Layout of the Islamic Mataram Palace in Plered: Reinterpreting Defence Aspects for Mitigation-Based Regional Planning - Wasita; Sunarningsih (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The palace, as a symbol of power, must be protected from various attacks by enemies/external parties. This effort is carried out by utilising various existing resources, both natural and those that must be provided. In this regard, a reinterpretation of the defence system of the Islamic Mataram Palace in Plered is necessary to explore spatial planning principles relevant to disaster mitigation-based regional planning. Therefore, the question raised in this paper is how the reinterpretation of the Islamic Mataram Palace’s defence system in Plered can be utilised for mitigation-based regional planning. This paper aims to identify and reconstruct the layered defence principles of the Plered Palace based on geographical and archaeological evidence as a model for flood mitigation. This paper uses a descriptive-analytical method. Data were collected from field observations and literature. The data are presented descriptively and pictorially. Furthermore, the data were analysed qualitatively by their context and function, and conclusions were drawn. The results show that the defence system at the Plered Palace was designed in an integrated manner, utilising the geographical conditions and enhancing it with the construction of a pool and surrounding fortifications (Cepuri). The fortifications were constructed of white stone and brick, arranged in thick walls. The combination of natural conditions, the pool, and the artificial fortifications created a layered defence pattern. The first and second layers were barriers, namely the river and the pool of Segoroyoso, and the third was the fortification as a final line of defence. Reinterpreting this layered fortification, it can be adapted into a flood mitigation-based planning concept for the Plered area. Flood mitigation utilises ponds or reservoirs, which is now called embung, to collect overflow from residential areas to the artificial lake of Segoroyoso, then joins the two rivers of Opak and Gajah Wong, and stream down to the sea. Research shows that the Plered Palace was built with security consideration aspects of the utilisation of both geographic (natural) and man-made (built) conditions, and those existences can be adapted for disaster mitigation in the modern era.